( x - 2/9 ) 2/36
ét o ét
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(1-x\right)^2=2003.\left(x-1\right)\)
\(\left(1-x\right)^2-2003\left(x-1\right)=0\)
\(\left(1-x\right)^2+2003\left(1-x\right)=0\)
\(\left(1-x\right)\left(1-x+2003\right)=0\)
\(\left(1-x\right)\left(2004-x\right)=0\)
\(TH1:1-x=0\)
\(x=1\)
\(TH2:2004-x=0\)
\(x=2004\)
vậy........
b: =>3x+9=0 và y^2-9=0 và x+y=0
=>x=-3; y=3
a: (2x-5)(y+3)=-22
mà x,y là số nguyên
nên \(\left(2x-5;y+3\right)\in\left\{\left(1;-22\right);\left(11;-2\right);\left(-1;22\right);\left(-11;2\right)\right\}\)
=>\(\left(x,y\right)\in\left\{\left(3;-25\right);\left(8;-5\right);\left(2;19\right);\left(-3;-1\right)\right\}\)
\(\dfrac{7}{5}x\dfrac{2}{5}=\dfrac{14}{25}\)
\(\dfrac{3}{4}+\dfrac{5}{4}:\dfrac{1}{4}x\dfrac{1}{2}=\dfrac{3}{4}+5x\dfrac{1}{2}=\dfrac{5}{2}\)
a, 5,6 x 2 + 2,8 x 8 + 11,2 x 2 - 48,5
= 11,2 + 11,2 x 2 + 11,2 x 2 - 48,5
= 11,2 x ( 1 + 2 + 2 ) - 9,7 x 5
= 11,2 x 5 - 9,7 x 5
= ( 11,2 - 9,7 ) x 5
= 1,5 x 5
= 7,5
b, 20,22 : 0,5 + 20,22 : 0,125 + 20,22 x 90
= 20,22 x 2 + 20,22 x 8 + 20,22 x 90
= 20,22 x (2 + 8 + 90)
= 20,22 x 100
= 2022
#Fox
a, 5,6 x 2 + 2,8 x 8 + 11,2 x 2 - 46
= 5,6 x 2 + 2,8 x 2 x 4 + 11,2 x 2 - 23 x 2
= 5,6 x 2 + 11,2 x 2 + 11,2 x 2 - 23 x 2
= 2 x ( 5,6 + 11,2 + 11,2 - 23 )
= 2 x 5 = 10
b, 20,22 : 0,5 + 20,22 : 0,125 + 20,22 x 90
= 20,22 x 2 + 20,22 x 8 + 20,22 x 90
= 20,22 x ( 2 + 8 + 90 )
= 20,22 x 100 = 2022
\(x-\dfrac{2}{9}=\dfrac{2}{36}\)
\(x=\dfrac{2}{36}+\dfrac{2}{9}\)
\(x=\dfrac{5}{18}\)